Development Of A Supervisory And Management Training Program For The Underground Coal Mining Industry - Paul E. Loustaunau; Catherine Wetherby; Devah Galloway (The National Institute for Occupational Safety and Health (NIOSH), 1983)
This report describes a project in which Development of a Supervisory and Management Training Program for the Underground Coal Mining Industry was developed and evaluated. The project was carried out in two phases. The first phase was a research effort to develop specifications for the program. The second phase was a development and evaluation effort. In the second phase, training programs for first-line supervisors (section foremen) and for middle managers (mine/shift foremen and mine superintendents) were prepared in accordance with the specifications and evaluated by members of the industry. This report describes the project and presents the conclusions drawn there from.